Pharmacological Inhibition of STAT3 by Stattic Ameliorates Clinical Symptoms and Reduces Autoinflammation in Myeloid, Lymphoid, and Neuronal Tissue Compartments in Relapsing–Remitting Model of Experimental Autoimmune Encephalomyelitis in SJL/J Mice - Khalid Alhazzani; Sheikh F. Ahmad; Naif O. Al-Harbi; Sabry M. Attia; Saleh A. Bakheet; Wedad Sarawi; Saleh A. Alqarni; Mohammad Algahtani; Ahmed Nadeem (Pharmaceutics, 2021)
Multiple sclerosis (MS) is an immune-mediated inflammatory disease that leads to demyelination and neuronal loss in the central nervous system. Immune cells of lymphoid and myeloid origin play a significant role in the initiation and amplification of neuronal inflammation in MS. STAT3 signaling plays a pivotal role in both myeloid and lymphoid immune cells, such as neutrophils and CD4+ T cells, through regulation of their inflammatory potential. Dysregulation in STAT3 signaling in myeloid and lymphoid cell compartments has been reported in MS. In this report, we attempted to investigate the effect of a small molecular inhibitor of STAT3, i.e., Stattic, in a relapsing–remitting (RR) model of experimental autoimmune encephalomyelitis (EAE). The effect of Stattic was investigated for clinical features, oxidative stress parameters, and Th17-related signaling in both the periphery and brain of SJL/J mice. Our data report that p-STAT3 expression is elevated in granulocytes, CD4+ T cells, and brain tissue in myelin proteolipid protein (PLP)-immunized SJL/J mice, which is associated with the presence of clinical symptoms and upregulation of inflammatory markers in these cells/tissues. Treatment with Stattic leads to the amelioration of disease symptoms and attenuation of inflammatory markers in neutrophils (iNOS/nitrotyrosine/IL-1β), CD4+ T cells (IL-17A/IL-23R), and brain tissue (IL-17A/iNOS/IL-1β/MPO activity/lipid peroxides) in mice with EAE. These data suggest that the blockade of STAT3 signaling in cells of lymphoid and myeloid origin may cause the attenuation of systemic and neuronal inflammation, which could be responsible for the amelioration of disease symptoms in an RR model of EAE. Therefore, pharmacological inhibition of STAT3 in RRMS could be a potential therapeutic strategy.